Factors influencing organizational performance in Perak Tengah administrative complex / Azzaim Shahrin Baharim - Baharim, Azzaim Shahrin (Universiti Teknologi Mara Perlis, 2020)
The main objective of this research is to study the factors influencing organizational performance in Perak Tengah Administrative Complex. The independent variables involved in this study recruitment and selection, training and development, performance appraisals, compensation, organizational design, communication, leadership, teamwork, decision making, culture, job satisfaction, motivation. Thepurpose of this research is to examine the relationship between independent variablesand dependent variables organizational performance, hence the hypothesis is noted.This research is carried out by using questionnaires as a part of the methodology ingathering data. The previous studies had been referred to construct the questionnaire.The sampling method of this research is simple random method. The total number ofrespondents are 85 people. The data collected has been analyzed through Statistical Package for Social Science (SPSS). Statistical Package for Social Science (SPSS) isapplied by the researchers to analyze the demographic data and also primary data.The discussion of this research objectives and recommendation for future researchwere included in this research as well.